Kinetic and Structural Study of Broccoli Myrosinase and Its Interaction with Different Glucosinolates - Castillo-Nara, A; Mahn-Osses, A; Roman-Aliste, J; Cottet-Bustamante, L (Elsevier Ltd, 2018)
Myrosinase is a glycosylated enzyme present in the Brassicaceae family that catalyzes the hydrolysis of glucoraphanin to yield sulforaphane, recognized as a health-promoting compound found in cruciferous foods. Broccoli myrosinase has been poorly characterized. In this work, the enzyme was purified from broccoli florets and its kinetic behaviour was analyzed. The cDNA of broccoli myrosinase was isolated and sequenced to obtain the amino acids sequence of the enzyme. A three-dimensional structural model of a broccoli myrosinase subunit was built and used to perform molecular docking simulations with glucoraphanin and other glucosinolates. Kinetic data were adjusted to the Two-Binding Sites Model that describes substrate inhibition, obtaining R2 higher than 97%. The docking simulations confirmed the existence of two substrate-binding sites in the monomer, and allowed identifying the residues that interact with the substrate in each site. Our findings will help to design strategies to better exploit the health-promoting properties of broccoli. © 2018 Elsevier Ltd